Pregunta
upstudy study bank question image url

Solve the equation. Enter any solution that checks as an integer or reduced fraction. Separate with commas if there is more than one solution. If there are no solutions, click the No Solution button. \( \frac{x}{x+2}+\frac{3}{x+7}=\frac{3 x-4}{x^{2}+9 x+14} \) One or more solutions:

Ask by Martinez Vaughn. in the United States
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

\( x = -5 \)

Solución

Solve the equation \( \frac{x}{x+2}+\frac{3}{x+7}=\frac{3x-4}{x^{2}+9x+14} \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{x}{x+2}+\frac{3}{x+7}=\frac{3x-4}{x^{2}+9x+14}\) - step1: Find the domain: \(\frac{x}{x+2}+\frac{3}{x+7}=\frac{3x-4}{x^{2}+9x+14},x \in \left(-\infty,-7\right)\cup \left(-7,-2\right)\cup \left(-2,+\infty\right)\) - step2: Multiply both sides of the equation by LCD: \(\left(\frac{x}{x+2}+\frac{3}{x+7}\right)\left(x+2\right)\left(x+7\right)=\frac{3x-4}{x^{2}+9x+14}\times \left(x+2\right)\left(x+7\right)\) - step3: Simplify the equation: \(x^{2}+10x+6=3x-4\) - step4: Move the expression to the left side: \(x^{2}+10x+6-\left(3x-4\right)=0\) - step5: Calculate: \(x^{2}+7x+10=0\) - step6: Factor the expression: \(\left(x+2\right)\left(x+5\right)=0\) - step7: Separate into possible cases: \(\begin{align}&x+2=0\\&x+5=0\end{align}\) - step8: Solve the equation: \(\begin{align}&x=-2\\&x=-5\end{align}\) - step9: Check if the solution is in the defined range: \(\begin{align}&x=-2\\&x=-5\end{align},x \in \left(-\infty,-7\right)\cup \left(-7,-2\right)\cup \left(-2,+\infty\right)\) - step10: Find the intersection: \(x=-5\) The solution to the equation \( \frac{x}{x+2}+\frac{3}{x+7}=\frac{3x-4}{x^{2}+9x+14} \) is \( x = -5 \).

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To solve the equation \( \frac{x}{x+2}+\frac{3}{x+7}=\frac{3 x-4}{x^{2}+9 x+14} \), we first recognize that the denominator on the right can be factored. The expression \( x^2 + 9x + 14 \) factors into \( (x + 2)(x + 7) \). Thus, we can rewrite the equation as: \[ \frac{x}{x+2} + \frac{3}{x+7} = \frac{3x - 4}{(x + 2)(x + 7)} \] To combine the left-hand side, we need a common denominator, which is \( (x + 2)(x + 7) \): \[ \frac{x(x + 7) + 3(x + 2)}{(x + 2)(x + 7)} = \frac{3x - 4}{(x + 2)(x + 7)} \] Now, simplify the numerator on the left: \[ x^2 + 7x + 3x + 6 = x^2 + 10x + 6 \] The equation now becomes: \[ \frac{x^2 + 10x + 6}{(x + 2)(x + 7)} = \frac{3x - 4}{(x + 2)(x + 7)} \] Setting the numerators equal gives: \[ x^2 + 10x + 6 = 3x - 4 \] Rearranging this, we get: \[ x^2 + 7x + 10 = 0 \] Now, factoring yields: \[ (x + 2)(x + 5) = 0 \] Thus, the solutions are \( x = -2 \) and \( x = -5 \). However, we must check for restrictions from the original equation. The denominators \( x + 2 \) and \( x + 7 \) cannot be zero, which means \( x \neq -2 \) and \( x \neq -7 \). Therefore, \( x = -2 \) is not valid. The only permissible solution is: \(-5\)

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad